ANTIFUNGAL SCREENING OF 61 TRADITIONAL MEDICINAL PLANTS OF 305 EXTRACTS AGAINST DERMATOPHYTIC FUNGI TRICHOPHYTON TONSURANS - Singh, P. Shivakumar; Vidyasagar, G. M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Antidermatophytic activity of 305 extracts from 61 traditional medicinal plants belonging to 33 different families from Hyderabad Karnataka region was subjected to screening against Trichophyton tonsurans. Methods: The screening was performed using Pet ether, chloroform, ethyalacetate, methanol and aqueous successive extracts (Soxhlet extractor) of each plant was tested for their antifungal activity using the agar well diffusion method at a sample concentration of 5 & 2.5 mg/ml. The minimum inhibitory concentrations of 10 very effective plants were determined using the broth dilution technique. Results: Out of 61 plants, 10 exhibited very effective antidermatophytic activity in three extracts like ethyalacetate (05), methanol (02), chloroform (02), Aqueous (01) extracts, effective activity observed in 14 plants in different extracts, whereas 34 plants showed moderate activity, 03 plants showed weak activity. Conclusion: On the basis of the results obtained, we conclude that the crude extracts of Allium sativam L., Corchorus oleterius L., Gymnosporia montana (Roth) Benth, Milletia pinnata (L.) Panigrahi, Lycopersicon esculentum L., Annona squamosa L., Plumbago zeylanica L., Calotropis gigantea L., Zingiber officinale Rosce. exhibited significant antidermatophytic activity (T. tonsurans) and properties that support folkloric use in the treatment of skin diseases as broad-spectrum antimycotic agents. This probably explains the use of these plants by the indigenous people against dermatological infections.